Food forensics and toxicology - Msagati, Titus A. M. (Wiley, 2017)
"A comprehensive guide, offering a toxicological approach to food forensics, that reviews the legal, economic, and biological issues of food fraud Food Forensics and Toxicology offers an introduction and examination of forensics as applied to food and foodstuffs. The author puts the focus on food adulteration and food fraud investigation. The text combines the legal/economic issues of food fraud with the biological and health impacts of consuming adulterated food. Comprehensive in scope, the book covers a wide-range of topics including food adulteration/fraud, food "fingerprinting" and traceability, food toxicants in the body, and the accidental or deliberate introduction of toxicants into food products. In addition, the author includes information on the myriad types of toxicants from a range of food sources and explores the measures used to identify and quantify their toxicity. This book is designed to be a valuable reference source for laboratories, food companies, regulatory bodies, and researchers who are dealing with food adulteration, food fraud, foodborne illness, micro-organisms, and related topics. Food Forensics and Toxicology is the must-have guide that: Takes a comprehensive toxicological approach to food forensics Combines the legal/economic issue of food fraud with the biological/health impacts of consuming adulterated food in one volume Discusses a wide range of toxicants (from foods based on plants, animals, aquatic and other sources) Provides an analytical approach that details a number of approaches and the optimum means of measuring toxicity in foodstuffs Food Forensics and Toxicology gives professionals in the field a comprehensive resource that joins information on the legal/economic issues of food fraud with the biological and health implications of adulterated food"- Resumé vydavatel
Keywords: toxikologie potravin; potravinářství -- zdravotní aspekty; alimentární intoxikace; podvody; kontrola potravin; food toxicology; food industry and trade -- health aspects; food poisoning; impostures; food quality control; monografie; případové studie; elektronické knihy; monographs; case studies; electronic books